EFL TEACHERS’ BELIEFS AND PRACTICES ON LEARNER AUTONOMY - Saraswati, Sonia (ENGLISH JOURNAL, 2019)
Learner autonomy which makes learner act more effectively has paid more attention in educational research and teaching practices in the 21st century. The aims of this study were to investigate the EFL teachers’ beliefs on learner autonomy and how their beliefs about this concept were applied in their teaching practices. The data were collected through qualitative methods by using questionnaire, interview guide and observation guide. The result of this recent study showed that the teachers had negative beliefs towards their students as autonomous learner. On the other hand, the teachers would like to have students to be more autonomous, but they are lack of understanding about the term of learner autonomy. It is indicated that teachers’ beliefs and practices failed in fostering learner autonomy in their contexts even when the policy is mandated by the government and their educational institutions.